Indoor environmental regulation hrough preference and behaviour of inhabitants in houses - Abdul Majid, Noor Hanita; Salehudin, Mohd Syafiq; Abdul Rahim, Zaiton; Othman, Rosniza (Elsevier, 2015)
Regulating the indoor environment for comfort and energy savings requires appropriate attitude and human behaviour of the house inhabitants. The aim of this study is to identify people’s main concerns when building or choosing a home. The research intends to determine how human behaviour regulates the indoor environmental conditions in houses towards achieving comfort and energy savings. A questionnaire survey was conducted through convenient sampling method with approximately 125 respondents. The results indicated the preferences for comfort and inhabitants’ attitude and behaviour in regulating the indoor environment.